Hematology and plasma biochemistries in the Blanding’s turtle (Emydoidea blandingii) in Lake County, Illinois - Mumm, Lauren E. (PLoS One, 2019)
Chelonians are one of the most imperiled vertebrate taxa on the planet due to changes in the environment, anthropogenic influences, and disease. Over the last two decades, conservation strategies including nest protection, head-starting and meso-predator control have been successfully adopted by the Lake County Forest Preserve District for a population of state-endangered Blanding’s turtles (Emydoidea blandingii) in Illinois. Only recently have efforts expanded to assess the effects of management action on turtle health. The objectives of this study were to 1) establish reference intervals for 16 hematologic and plasma biochemical analytes in free-ranging Blanding’s turtles, 2) characterize demographic and temporal drivers of clinical pathology values including age class, sex, month, and year, and 3) describe bloodwork differences between a managed (SBCP) and unmanaged (IBSP) study site. Hematology and plasma biochemistries were performed for 393 turtles from 2017–18 at two sites in the Lake Plain region. Subject or population-based reference intervals were established based on the index of individuality per American Society for Veterinary Clinical Pathology guidelines. Analytes differed by age class [packed cell volume (PCV), total solids (TS), total white blood cell counts (WBC), heterophils, lymphocytes, heterophil:lymphocyte ratio (H:L), total calcium (Ca), calcium:phosphorous (Ca:P), bile acids (BA), aspartate aminotransferase (AST)], sex [H:L, Ca, phosphorus (P), Ca:P, creatine kinase (CK)], month [eosinophils, H:L, Ca, P, uric acid (UA), AST], and year [PCV, WBC, lymphocytes, basophils, H:L, Ca, P, UA]. Several analytes also varied by site [PCV, TS, monocytes, eosinophils, P, UA, AST], suggesting that health status may be affected by habitat management or lack thereof. The results of this study provide a baseline for ongoing health assessments in this region as well as across the Blanding’s turtle range.